PERANCANGAN APLIKASI KASIR BERBASIS WEB MENGGUNAKAN PHP DAN MYSQL (Studi Kasus: Toko Pandawa) - Nugraha, Agung; Budiman (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The rapid advancement of information technology has significantly transformed business operations, including transaction management in retail stores. Many small and medium-sized enterprises (SMEs) still rely on manual systems, which are prone to inefficiencies, human errors, and difficulties in generating accurate financial reports. This study aims to design and implement a web-based cashier application for Toko Pandawa, a retail business in Majalengka, to improve transaction processing, inventory management, and reporting. The research employs the Waterfall development methodology, consisting of requirement analysis, system design, implementation, testing, and maintenance. Data collection was conducted through interviews, direct observation, and literature studies to identify the store’s operational problems and user requirements. The system was developed using PHP as the programming language and MySQL as the database management system, while Visual Studio Code served as the development environment. Unified Modeling Language (UML) diagrams, including use case, activity, sequence, and class diagrams, were used to model the system. The resulting application provides features for transaction recording, stock monitoring, report generation, and store management. Functional testing using the Black Box method showed that all modules worked as expected, ensuring system reliability and usability. This research demonstrates that web-based cashier applications can enhance efficiency, reduce errors, and support better decision-making for SMEs.